Creating effective peer observation faculty training through a community of practice - Alfred Bundrick; Becky A Tugman; Lauren E Stephens; Taimi Olsen (To Improve the Academy, 2025)
Peer observation of teaching (PoT) is a recognized evaluation tool. However, faculty concerns persist regarding bias, beneficial feedback, and lack of peer observer training. While faculty desire to provide quality and equitable reviews, many higher education faculty peers have little expertise in conducting observations and evaluations. This article proposes a comprehensive approach to enhance the quality and fairness of PoT in higher education through the use of a community of practice model, aligning it with the evolving needs of teaching evaluation processes. The authors share their growth process from an ad hoc committee into a long-term organic community of practice to meet formative and summative observations of teaching needs. Based on literature supporting PoT steps, the collaborative vision between the faculty and the Center for Teaching and Learning director resulted in a supportive model for reviews that provided faculty with feedback and professional growth. The training model starts with new members experiencing the observational process, completing an in-depth practicing PoT training, pairing with experienced peers to grow confidence, and then eventually training new members.